Short term variability in FEV1 and bronchodilator responsiveness in patients with obstructive ventilatory defects. Issue 7 (July 1987) - Tweeddale, P M; Alexander, F; McHardy, G J
Abstract : Short term variability in FEV1 and responsiveness to inhaled bronchodilator were measured in 150 patients with obstructive ventilatory defects. The range of initial FEV1 was 0.5-4.71 and the natural variability over a 20 minute period when expressed in absolute terms was similar over the entire range, and differed insignificantly from that found in normal subjects. The increase in FEV1 and vital capacity (VC) required to exclude natural variability with 95% confidence in these patients was 160 ml and 330 ml respectively. Natural variability when expressed in percentage terms was negatively correlated with the level of FEV1 recorded. The analysis of changes in FEV1 and VC after administration of bronchodilator used absolute and percentage criteria for response. The number of responders differed considerably according to the criterion used. In those defined by the absolute criterion as responders there was no evidence that size of response was related to level of FEV1. Percentage criteria have traditionally been used to identify responses to bronchodilator that may be clinically useful, while absolute criteria, although statistically valid, have not been favoured. Reappraisal of the criteria used and their limitations and implications is required.